Spectrum Policy on Broadband Market To Reduce Digital Divide and Promote Market Competition - Xin Tang; Bronwyn Howell (International Telecommunications Society (ITS), 2022)
A necessary condition for digital transformation is ubiquitous access to high-quality communications networks, leading to the construction of communications infrastructure accessible to all citizens featuring prominently in the policy agendas of many countries. In New Zealand, this is reflected in the investment focus of the country's Ultra-Fast-Broadband (UFB) program aiming to roll out FTTP to 87% of households by 2022, and the Rural Broadband Initiative (RBI) improving mobile network connectivity in underserved and unserved locations. In recent years, technological innovation has led to new network typologies and changing cost structures for all network types. These innovations raise questions about whether the appropriate policy response to reduce "digital divides" in access to infrastructure should be to pay specific firms to build predetermined infrastructures. This paper will use New Zealand's policy context of the UFB and RBI, and existing spectrum policy framework, to explore policy options for addressing digital divides. The inquiry uses Causal Loop Diagram (CLD) modelling as a tool to inform policy development and assessment. The CLD models will capture the interactions between policy, market, regulations and technologies, and allow comparative evaluation of the expected effects of different interventions. In particular, the models will explore how new technologies and spectrum policy influence competition between different network types.
Keywords: 330; Spectrum Policy; FTTP; FWA; LEO satellite; network sharing; spectrum sharing; digital divide